2021
DOI: 10.3390/ijms222111693
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Fine Mapping of a Locus Related to Leaf Up-Curling Trait (Bnuc3) in Brassica napus

Abstract: Leaf trait is an important target trait in crop breeding programs. Moderate leaf curling may be a help for improving crop yield by minimizing the shadowing by leaves. Mining locus for leaf curling trait is of significance for plant genetics and breeding researches. The present study identified a novel rapeseed accession with up-curling leaf, analyzed the up-curling leaf trait inheritance, and fine mapped the locus for up-curling leaf property (Bnuc3) in Brassica napus. Genetic analysis revealed that the up-cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Thus, the up-curling leaf trait should be explored in more detail. To date, three loci related to the up-curling leaf trait have been identified in B. napus (i.e., BnUC1 , BnUC2 , and BnUC3 ) [ 39 , 40 , 41 ]. In present work, we found that the Bnud1 mutant had an increased photosynthetic efficiency at seedling stage, and relatively small plant architecture ( Figure 1 ; Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the up-curling leaf trait should be explored in more detail. To date, three loci related to the up-curling leaf trait have been identified in B. napus (i.e., BnUC1 , BnUC2 , and BnUC3 ) [ 39 , 40 , 41 ]. In present work, we found that the Bnud1 mutant had an increased photosynthetic efficiency at seedling stage, and relatively small plant architecture ( Figure 1 ; Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf morphological mutations in B. napus (e.g., upward and downward curling and wrinkling) are related to photosynthetic efficiency and affect the yield. Previous research on leaf curling revealed the associated loci and genes, including a dominant locus ( BnDWF/DCL1 ) [ 36 ], semi-dominant genes ( sca and ds-4 ) [ 37 , 38 ], and the genes ( BnUC1 , BnUC2 , and BnUC3 ) [ 39 , 40 , 41 ] responsible for the up-curling of B. napus leaves. Analyses of gene functions demonstrated that abnormalities in some leaf flatness-related traits are caused by the deficient expression of genes encoding proteins mediating phytohormone (e.g., auxin and brassinolide) biosynthesis or signaling [ 13 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In monocotyledonous plants, such as rice, the phenotype of leaf curling, in general, is caused by the change of bulliform cells ( Li et al., 2010 ; Fang et al., 2012 ; Li et al., 2016 ; Sun et al., 2020 ; Xu et al., 2021 ). On the other hand, leaf curling in dicotyledonous plants is mainly related to the adaxial–abaxial leaf polarity establishment, cutin and cuticular wax biosynthesis, and hormone responses ( Wan et al., 2021 ). The first gene associated with leaf polarity, phantastica ( PHAN ), was required for the elaboration of the proximodistal axis ( Waites and Hudson, 1995 ; Waites et al., 1998 ).…”
Section: Introductionmentioning
confidence: 99%